2016
DOI: 10.5380/ce.v21i2.42845
|View full text |Cite
|
Sign up to set email alerts
|

Fatores De Risco Para Sepse Neonatal Em Unidade De Terapia: Estudo De Evidência

Abstract: RESUMEN: Revisión integrativa de literatura cuya finalidad fue presentar las principales evidencias de factores de riesgo para sepsis neonatal en recién nacidos internados en Unidad de Terapia Neonatal. La búsqueda fue hecha entre los meses de julio y agosto de 2015, en las bases de datos Scientific Eletronic Library Online, SciVerse Scopus y PubMed, utilizándose los descriptores: factores de riesgo, unidad de terapia intensiva neonatal, recién nacido; y las siguientes palabras claves: sepsis neonatal y premat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
1
2
0
3
Order By: Relevance
“…Among the aspects related to the infection of NB, the following were identified gestational age < 37 weeks from 42 (93.3%), low birth weight between < 750g to 1.499g, in this study 33 were found (73,3%) in this weight range. These findings corroborate the literature, which points to prematurity as one of the factors linked to the occurrence of infections in the neonatal period (COSTA et al, 2016;DE OLIVEIRA, 2016). Furthermore, 35 (77.7%) NB were submitted to some type of CVC during admittance, of these, 22 (48.8%) used PICC, 4 (8.8%) UC and 9 (20.0%) SLC.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Among the aspects related to the infection of NB, the following were identified gestational age < 37 weeks from 42 (93.3%), low birth weight between < 750g to 1.499g, in this study 33 were found (73,3%) in this weight range. These findings corroborate the literature, which points to prematurity as one of the factors linked to the occurrence of infections in the neonatal period (COSTA et al, 2016;DE OLIVEIRA, 2016). Furthermore, 35 (77.7%) NB were submitted to some type of CVC during admittance, of these, 22 (48.8%) used PICC, 4 (8.8%) UC and 9 (20.0%) SLC.…”
Section: Discussionsupporting
confidence: 89%
“…2020 http://dx.doi.org/10.14393/BJ-v36n6a2020-49980 together with underreporting. For this reason, one cannot state that the mortality rate is exclusively related to infection (DE OLIVEIRA et al, 2016;BRITO et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A infecção apresenta sinais e sintomas inespecíficos, muitas vezes silenciosos, confundindo-se com as próprias condições da prematuridade, como alterações respiratórias. Pode ter início precoce, com manifestação em até 48 horas de vida, e após esse tempo caracteriza-se como um acontecimento tardio, devido ao contato com patógenos após o nascer (15) . As infecções primárias de corrente sanguínea são as principais infecções em UTIN, sendo associadas a altos custos hospitalares.…”
Section: Discussionunclassified
“…que antecederam o nascimento, assistência prestada e condições socioeconômicas dos locais dos estudos em comparação. 4,7,[10][11][12][13][14] Neste estudo, a idade gestacional mostrou-se um fator importante relacionado ao óbito, pois 64% dos óbitos dos RN diagnosticados com sepse ocorreram naqueles com idade gestacional menor que 30 semanas, classificados como prematuros extremos. A literatura mostra que a prematuridade é um fator de risco para o desenvolvimento de sepse, 15,16 assim como a sepse neonatal e a própria prematuridade são fatores de risco para óbitos neonatais.…”
Section: Discussionunclassified